Multi-objective time–cost trade-off optimization for the construction scheduling with Rao algorithms. (February 2023) - Yılmaz, Mehmet; Dede, Tayfun
Abstract: Determining the time and cost of activities is one of the most important stages of construction project planning. Measures taken to shorten the time, such as the need for more or more qualified employees, equipment and machinery, increase project direct cost. The process of deciding which option to use in activities with more than one time–cost option has revealed the time–cost trade-off problem which is discrete optimization. Within the scope of this study, the non-dominant sorting (NDS) method is integrated into the Rao-1 and Rao-2 algorithms and applied to small and medium-scale problems. The numerical results show that the NDS-Rao-2 algorithm has found a better result with a significant number of function evaluations compared to algorithms such as PSO, ACO, GA and TLBO used in previous studies. In addition, the NDS-based Rao-2 algorithm not only find optimal /near results, but also suggest more than one pareto result to the decision maker for time–cost trade-off problem. For this reason, the developed multi-objective Rao-2 algorithm can be considered as a very good alternative for time–cost trade-off problems which are combinatorial problems.